Feedback mechanisms and consumer satisfaction, trust and repurchase intention in online retail. Issue 3 (3rd July 2018) - Wang, Hongpeng; Du, Rong; Olsen, Timothy
ABSTRACT: We introduce a key construct, perceived effectiveness of feedback mechanisms (PEFMs), to analyze moderating effects of PEFMs on the relationship between consumers' satisfaction, trust, and repurchase intention. We find that (1) PEFMs negatively moderate the satisfaction–trust relationship; (2) PEFMs positively moderate the trust–repurchase intention relationship; (3) provider recommendations and customer reviews are complementary with customers' trust but can substitute for prior experience with products.